2014
DOI: 10.1007/s00431-014-2477-1
|View full text |Cite
|
Sign up to set email alerts
|

Cushing syndrome after bilateral lensectomy

Abstract: Iatrogenic Cushing syndrome induced by oral and parenteral corticosteroid administration is a well-known complication, and necessary precautions have to be taken. Cushing syndrome, however, following treatment with glucocorticoid-containing eye drops is a very rare complication. To the best of our knowledge, there have been only four reported cases in the literature. Herein, we present an infant boy who developed Cushing syndrome after receiving dexamethasone-containing eye drops after bilateral cataract extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In one study, the prolonged use of 0.1% fluorometholone was beneficial for the prevention of rejection after penetrating keratoplasty and no adverse systemic side effects were reported 34. Even endocrinological side effects from eye drops containing dexamethasone have also been described in clinical trials, albeit rarely and certainly are negligible 35,36…”
Section: Drug Classesmentioning
confidence: 99%
“…In one study, the prolonged use of 0.1% fluorometholone was beneficial for the prevention of rejection after penetrating keratoplasty and no adverse systemic side effects were reported 34. Even endocrinological side effects from eye drops containing dexamethasone have also been described in clinical trials, albeit rarely and certainly are negligible 35,36…”
Section: Drug Classesmentioning
confidence: 99%
“…To the best of our knowledge, fewer than 10 cases of CS developing following ocular steroid application have previously been reported . The clinical and hormonal profiles of these cases are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…14 To the best of our knowledge, fewer than 10 cases of CS developing following ocular steroid application have previously been reported. [2][3][4][5][6][7][8][9][10] The clinical and hormonal profiles of these cases are summarized in Fluorometholone has been administered in a range of indications. One study reported that allergic conjunctivitis was the second most common indication of fluorometholone use in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations